Molecular Characterization of Waa Genes (waaA, waaC, wamB, wabG) Participate in Core Biosynthesis in P.mirabilis LPS - S.H. , Ruaa; F. Darweesh, Mayyada (International Journal of Psychosocial Rehabilitation, 2020)
LPS is a potential Proteus virulence factor that plays a key role in pathogenesis as well as in stimulating innate immune response. The structure of lipopolysaccharide differs from one bacterium to another, dependent on enzymes and gene products that can modify the basic structure of lipopolysaccharide in some bacteria, especially pathogens. So this study aimed to detect the present waa genes (waaA, waaC, wamB, wabG) that are involved in the biosynthesis of core LPS. 50 isolates of P. mirabilis were isolated from 200 urine specimens taken from recurrent urinary tract infection (UTI) patients attended to at AL-Sadar Hospital. Specimens were cultured on specific media, and then bacterial isolates were identified depending on morphological, biochemical, and VITK-2. The results showed that the P. mirabilis comprise 11 (22%), 30 (30%), and 9 (18 %) from recurrent UTI, kidney stone, and catheter samples, respectively. The isolates that appeared multidrug-resistant to all antibiotics used in this study were chosen to extract lipopolysaccharide. Then this specimen was used for studies the genes responsible for synthesis of LPS; this specimen give positive result for waaA, waaC, wamB and wabG